Detection of Extended Spectrum Bet-Lactamases in Clinical Isolates of Escherichia coli and Klebsiella pneumoniae in Asia-Pacific Region - M Chitsaz; JM BELL; JD Turnidge; MD Barton; M Bazargan (Tehran University of Medical Sciences, 2007)
Background: The CLSI screening and confirmatory methods are recommended by CLSI for detection of extended- spectrum β- lactamases in Escherichia coli (ECOL), Klebsiella pneumoniae (KPNE) and Klebsiella oxytoca. It is recommended that screening be performed routinely in these species, and if the screening test is positive, that a confirmatory test be undertaken. The CLSI standards do not currently provide advice on what to do with screen positive, confirmatory test-negative strains. Methods: All isolates of ECOL and KPNE collected as part of the SENTRY APAC region surveillance, 1998 to 2003, that had MICs by the CLSI broth microdilution method to ceftriaxone, ceftazidim and aztreonam with a MIC above 1 mg/L to any of these three were subjected to confirmatory testing as per CLSI method, except that ceftriaxon replaced cefotazime. Selected isolates were subjected to PCR for detection of β- lactamase genes belonging to TEM, SHV, and family specific group CTX-M and plasmid-mediated AmpC β-lactamase. Results: Overal 8.9% of 4,515 ECOL and 20.3% of 2,081 KPNE collected over 6- year period were screen positive (P+). The presence of an ESBL was not confirmed (P+C -) in over 30% and 15% of the screen positive ECOL and KPNE respectively. Over 60% of P+C- ECOL had a plasmid-mediated AmpC β-lactamase (65% of which belonged to the CIT group), while in KPNE, 74% of the P+C- strains contained AmpC (89% DHA group) either alone or in combination with TEM or SHV genes. AmpC was strongly associated with ceftazidime rather than ceftriaxone non-susceptibility with (MIC> 8 mg/L) in both species. Conclusion: There is a high prevalence of non-ESBL β-lactameses, especially AmpC, in ECOL and KPNE with elevated MICs (2-8 mg/L) in the Asia-Pacific region.